2020
DOI: 10.22271/phyto.2020.v9.i5u.12550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macronutrients, microbial consortium and biostimulants on growth and yield of African marigold (Tagetes serecta L.)

Abstract: The present study was undertaken to bring out the best combination of microbial consortium on effect of biostimulant for the growth and yield of African marigold (Tagetes erecta L.) hybrid L3. The experiment was conducted in open field condition in a randomized block design with 10 treatments combinations and replicated thrice at ICAR-KVK, Bagalkot during the year 2017. Application of bio-control agents viz., Trichoderma harzianum, Pseudomonas fluorescens, Bacillus subtilis were applied in different combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Cauliflower stands out as particularly sensitive to molybdenum deficiency, with symptoms such as whiptail deformation and inhibited head development observed in affected plants (Sharma, 2002). Molybdenum facilitates the utilization of soilabsorbed nitrates by plants, thereby impacting vegetative growth and yield potential (Ranjan et al, 2020). Studies have demonstrated the beneficial effects of foliar applications of boron and molybdenum in enhancing cauliflower yield and vegetative growth (Ranjan et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cauliflower stands out as particularly sensitive to molybdenum deficiency, with symptoms such as whiptail deformation and inhibited head development observed in affected plants (Sharma, 2002). Molybdenum facilitates the utilization of soilabsorbed nitrates by plants, thereby impacting vegetative growth and yield potential (Ranjan et al, 2020). Studies have demonstrated the beneficial effects of foliar applications of boron and molybdenum in enhancing cauliflower yield and vegetative growth (Ranjan et al, 2020).…”
mentioning
confidence: 99%
“…Molybdenum facilitates the utilization of soilabsorbed nitrates by plants, thereby impacting vegetative growth and yield potential (Ranjan et al, 2020). Studies have demonstrated the beneficial effects of foliar applications of boron and molybdenum in enhancing cauliflower yield and vegetative growth (Ranjan et al, 2020).…”
mentioning
confidence: 99%